Pengangkatan Anak tanpa Penetapan Mahkamah Syar’iyah: Aktivitas Sosial, Kepastian Hukum di Nagan Raya, Aceh - Syarifah Rahmatillah; Mahlil Ridwan (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2022)
Child raising is the transfer of the legal position of the child from the parent to the parent. In practice, the raising of children is usually carried out by persons who, in their marriage, do not produce offspring. The process of raising children in Indonesia has been regulated in PP No. 54 of 2007 on the Enforcement of Child Abduction and Permensos No. 110 of 2009 on the Conditions of Deprivation of Children. However, in practice, many children are raised by society in ways that are not in accordance with the rules. The problem that is investigated in this script is how the raising practices are carried out by the people of Kecamatan Tadu Raya and how the review of the Indonesian legal system is related to the implementation of the raising of children carried out in Kecamatan Tudu Raya. In this study, the author uses the method of the Yuridis empirical approach, which is to study the norms or rules that form the foundation and see the application of these rules in the life of society. The findings of this study revealed that child raising in the district of Tadu Raya is only implemented through the process of oral agreement between the parent raising with the parent of the child with the factor has not yet had children in the family, as well as the economic factor of the family raising the sense of disappointment to raise the child, the parent is also positioned as a child even though the relationship with the parents of his child is not decided. According to the Indonesian legal system, the practice of raising a child is not in accordance with positive law and Islamic law. So the practice of raising children in the Tadu Raya is only a social activity that does not follow the applicable legal process.